2022
DOI: 10.1039/d2cy00357k
|View full text |Cite
|
Sign up to set email alerts
|

Insight into the pH effect on the oxygen species and Mn chemical valence of Co–Mn catalysts for total toluene oxidation

Abstract: Mn-based metal oxides have shown promising performance in catalytic oxidation of toluene since the mixed valences of Mn3+ and Mn4+ on the surface. Herein, a series of Co-Mn catalysts were...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 67 publications
0
6
0
Order By: Relevance
“…4,5 Presently, two varieties of catalysts have been established for the total conversion of toluene,, namely supported noble metals (Ag, Au, Pt and Pd) [6][7][8][9] and metal oxides. [10][11][12][13][14][15] Particularly, Transition metal oxides (TMOs) especially possesses the advantages of availability, low cost, high thermal stability, considerable reducibility, strong resistance to poisons and promising catalytic performance. [16][17][18] Therefore, TMOs have received much attention in the total abatement of VOCs.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…4,5 Presently, two varieties of catalysts have been established for the total conversion of toluene,, namely supported noble metals (Ag, Au, Pt and Pd) [6][7][8][9] and metal oxides. [10][11][12][13][14][15] Particularly, Transition metal oxides (TMOs) especially possesses the advantages of availability, low cost, high thermal stability, considerable reducibility, strong resistance to poisons and promising catalytic performance. [16][17][18] Therefore, TMOs have received much attention in the total abatement of VOCs.…”
Section: Introductionmentioning
confidence: 99%
“…To date, several binary metal-doped (Mn, Cu, Ni, and Fe) Co3O4 thin films and nanocrystals powder were prepared and successfully tested as catalysts. 13,15,22 Among of TMOs-based catalysts, Co-Cu and Co-Fe oxide catalysts have exhibits promising performance in the elimination of VOCs. In fact, by introducing different types of transition metals (TMs) into the pure TMOs lattice, the redox behaviour and chemical activity of the obtained mixed-TMOs can be modify due to many factors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To the best of our knowledge, the current research of ternary Mn spinels, however, has been unable to develop synthetic methods to produce small, colloidally stable, low-dispersity nanocrystals. Of particular interest is the CMO family of spinels, known for their superior electrocatalytic and supercapacitor performance. ,, ,,,, Previous work using hydrothermal/solvothermal, solid-state, ,, co-precipitation, ,, or solvent-assisted ,, methods to generate CMO spinels has resulted in large, ,,,,, aggregated ,,,, nanocrystals with poor size control. Additionally, methods like solvothermal and hydrothermal reactions make optimization and scaling more difficult because of the need for a pressurized vessel, which leads to the inability to take reaction aliquots, thus restricting the determination of the onset of Ostwald ripening. …”
Section: Introductionmentioning
confidence: 99%
“…Two types of catalyst have been developed for the lowtemperature oxidation, namely supported precious metals (Ag, Au, Pt and Pd) [6][7][8][9] and mixed metal oxides. [10][11][12][13][14] Several studies on the total oxidation of DME over Au, Pt, Pd, Rh, and Ru catalysts supported on different oxides including Al 2 O 3 , ZrO 2 , TiO 2 and CeO 2 have been performed 6,[15][16][17][18][19] and the results revealed that Ru and Pt catalysts supported on Al 2 O 4 exhibit total oxidation of DME to CO 2 and H 2 O within the temperature range from 400 to 600 °C, which is not satisfactory for low-temperature activity. In addition, the disadvantages of noble metals are their higher cost, poor availability, poisoning tendency and unsuitable and expensive investment for industrial applications.…”
mentioning
confidence: 99%